Recent Advances in Kidney Bioengineering - Cintron Pregosin, Nina; Bronstein, Robert; Mallipattu, Sandeep K. (Frontiers in Pediatrics, 2021)
Kidney disease is an epidemic that affects more than 600 million people worldwide. The socioeconomic impacts of the disease disproportionately affect Hispanic and non-Hispanic Black Americans, making the disease an issue of social inequality. The urgency of this situation has only become worse during the COVID-19 pandemic, as those who are hospitalized for COVID-19 have an increased risk of kidney failure. For researchers, the kidney is a complex organ that is difficult to accurately model and understand. Traditional cell culture models are not adequate for studying the functional intricacies of the kidney, but recent experiments have offered improvements for understanding these systems. Some recent progress includes improved cell culture methods, organoid modeling, the integration of 3D printing, decellularization, and the use of microfluidic chips. Here, we offer a review of the most recent advances in kidney bioengineering.